Asymptomatic carotid disease and cardiac surgery consensus - Stansby, G; Macdonald, S; Allison, R; de Belder, M; Brown, M; Dark, J; Featherstone, R; Flather, M; Ford, G; Halliday, A; Malik, I; Naylor, R; et al. (Sage Publications, 2011)
The Carotid Disease and Cardiac Surgery Consensus Meeting was convened as a multidisciplinary gathering to consider the management of patients undergoing cardiac surgery who are found to have asymptomatic carotid artery disease. There are no randomized trials concerning whether carotid interventions are of value in this situation and the natural history is unclear. Bilateral carotid artery disease (≥70% stenosis) should be regarded clinically relevant when considering hemodynamic and short-term surgical stroke risk. However, this may be because the presence of significant carotid disease is also a marker for aortic arch and intracerebral disease. A natural history study is urgently needed to determine the incidence, predictive factors, and natural history of asymptomatic carotid disease in patients undergoing contemporary cardiac surgical interventions to inform the design of any future randomized trial.